SYNTHESIS OF NICKEL CONTAINING PIG IRON (NCPI) BY USING LIMONITE TYPE OF LATERITIC ORE FROM SOUTH EAST SULAWESI - Solihin Solihin (Indonesian Institute of Sciences, 2015)
ABSTRAK Nickel contain pig iron (NCPI) merupakan bahan baku penting dalam pembuatan baja tahan karat dan baja paduan lainnya. Sumber alami NCPI adalah bijih laterite. Cadangan bijih laterit dalam jumlah besar telah ditemukan di Provinsi Sulawesi Tenggara. Bijih laterit kadar tinggi dari wilayah ini telah diproses untuk menghasilkan ferronikel, sedangkan bijih laterit kadar rendah, karena kadar nikelnya yang terlalu rendah, tidak digunakan dalam pembuatan ferronikel. Dalam penelitian ini bijih laterit kadar rendah telah dicoba dimanfaatkan sebagai bahan baku dalam pembuatan NCPI. Terhadap bijih laterit dilakukan proses reduksi pada berbagai temperatur. Hasil pengamatan menunjukan bahwa reaksi reduksi meningkat seiring dengan naiknya temperatur proses. Pada temperatur 1200oC telah tebentuk secara signifikan fasa logam. Hasil peleburan terhadap hasil reduksi menghasilkan NCPI dengan kadar nikel dan besi masing-masing 3,7 dan 86,8%. Analisa morfologi terhadap hasil peleburan menunjukan bahwa NCPI yang dihasilkan mengandung lapisan kaya besi-kromiun dan butiran besi kromium yang kaya belerang dalam matrik paduan besi nikel. Abstract Nickel containing pig iron (NCPI) is one of important materials for stainless steel and other iron-nickel alloys production. The natural source of NCPI in Indonesia is laterite ore. Large deposit of laterite ore has been found in South East Sulawesi. High grade laterite ore (saprolitic type of laterite ore) in this region has been used for ferronickel making, whereas low grade laterite ore (limonitic type of laterite ore) has not been processed, due to its too low nickel content. Through this recent research, low grade laterite ore has been utilized as raw material in nickel pig iron making experiment. Laterite ore was reduced by carbon at various temperatures. It has been found that reduction reaction increases with an increasing in temperature. At 1200oC, metal phase has been formed significantly. The melting of reduced ore results in NCPI that contains 3.17% nickel and 86.8% iron. The analysis to NCPI morphology shows that microstructure of NCPI consist of iron-chromium layer and rich sulfur iron chromium grain in the matrix of iron nickel.